The Effect of Moringa Leaf Flour in Rations on Male Quail Performance: Pengaruh Tepung Daun Kelor dalam Ransum terhadap Performa Puyuh Jantan - Sari, Vera Ateka; Kaharuddin, Desia; Santoso, Urip (Buletin Peternakan Tropis, 2025)
This study aims to evaluate the use of moringa leaf flour on the growth of male quail. The design used in this study was a Completely Randomized Design with 4 treatments, 5 replications and each replication consisted of 8 quails. The four treatments were rations without Moringa leaf flour (P0); 5% Moringa leaf flour (P1); 10% Moringa leaf flour (P2) and 15% moringa leaf flour (P3). The findings indicated that the inclusion of moringa leaf flour did not significantly influence feed intake, weight, or feed conversion ratio (P>0.05), but it did have a significant impact (P<0.05) on the body weight and weight gain of male quail. Thus, Moringa leaf flour can be given as much as 10% without reducing the performance of male quails